Practical financial management - Lasher, William (Cencage Learning, 2017)
Let a professor who used to be a financial executive and CFO introduce you to todays most important financial management topics within the pages of PRACTICAL FINANCIAL MANAGEMENT, Eighth Edition. Author William R. Lasher uses his experience as a CFO to give you an insiders look into the issues and challenges facing financial managers every day. From hidden agendas to decision maker biases and their effect on the analyses of financial proposals, you will see principles in action in this dynamic text. You will examine the latest developments, like activist